2015
DOI: 10.1371/journal.pone.0145303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Natal Vitamin D Supplementation with Partial Correction of Vitamin D Deficiency on Early Life Healthcare Utilisation: A Randomised Controlled Trial

Abstract: BackgroundSome observational studies have suggested that higher prenatal Vitamin D intake may be associated with improved health outcomes in childhood. However there have been mixed results in this area with some negative studies, especially for effects on atopic and respiratory outcomes. We examined the effect of prenatal Vitamin D on healthcare utilisation in the first three years of life.MethodsIn an ethnically stratified randomised controlled trial conducted at St Mary’s Hospital London, 180 women at 27 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…The studies evaluated the effect of vitamin D supplementation during pregnancy on 14 health outcomes in newborns and infants: length, weight, and head circumference at birth (nine studies), [10][11][12][13][14][15][16][17][18] vitamin D concentration (22 studies), calcium concentration, bone and dental health (seven studies), 14,18,[39][40][41][42][43] respiratory disease and wheezing (respiratory tract infections) (five studies), [44][45][46][47][48] use of health services (one study), 49 DNA methylation (two studies), 47,50 genetic variations of vitamin D-binding protein (one study), 51 insulin-like growth factor (IGF) at birth (one study) 52 , and instestinal microbiota (one study). 53 The studied samples were predominantly composed of newborns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies evaluated the effect of vitamin D supplementation during pregnancy on 14 health outcomes in newborns and infants: length, weight, and head circumference at birth (nine studies), [10][11][12][13][14][15][16][17][18] vitamin D concentration (22 studies), calcium concentration, bone and dental health (seven studies), 14,18,[39][40][41][42][43] respiratory disease and wheezing (respiratory tract infections) (five studies), [44][45][46][47][48] use of health services (one study), 49 DNA methylation (two studies), 47,50 genetic variations of vitamin D-binding protein (one study), 51 insulin-like growth factor (IGF) at birth (one study) 52 , and instestinal microbiota (one study). 53 The studied samples were predominantly composed of newborns.…”
Section: Resultsmentioning
confidence: 99%
“…50 Regarding inter ventions tested in the 44 trials, seven started vitamin D supplementation in the first trimester of pregnancy, 18,27,37,38,47,51,53 21 in the second, 13,[15][16][17]22,25,26,28,29,[31][32][33]36,[40][41][42][43]46,48,50,52 and 16 in the third. [10][11][12]14,[19][20][21]23,24,30,34,35,39,44,45,49 The studies that started supplementation in the first trimester found a statistically significant difference in weight, 18 height, 18 fontanelle size, 18 vitamin D2 concentration, 7,3...…”
Section: Resultsmentioning
confidence: 99%
“…Two randomized controlled trials have assessed HSU following vitamin D supplementation in pregnancy. Griffiths supplementation (placebo, 20 µg/d (800 IU/d) or a single bolus of 5000 µg (200 000 IU)) from 27 weeks to delivery influenced overall HSU in children from in London, England in the first 3 years (2) . They also found no association between 25-hydroxyvitamin D concentrations in the children at age 3 years (n 65) and HSU.…”
Section: Discussionmentioning
confidence: 99%
“…Upper respiratory tract infections (URTI) are the most common infectious disease for children in North America and account for a large portion of health-service utilization (HSU) (1) . Pre-school children experience six to eight URTI per year (2) , with approximately 50 % seeking medical attention in the outpatient or emergency department setting and roughly 1 % requiring hospitalization (3)(4)(5)(6) . A number of studies have suggested that low vitamin D levels may play a role in susceptibility to URTI in children.…”
mentioning
confidence: 99%
“…Além disso, níveis baixos de VD durante o desenvolvimento pulmonar pode afetar o crescimento pulmonar pós-natal e aumentar o risco de desenvolver doença pulmonar 74 . A suplementação materna da VD, particularmente em mães com níveis iniciais de 25[OH]D superiores a 30 ng/mL, diminui asma / sibilância recorrente na prole ao longo dos 3 primeiros anos de vida, sugerindo que é necessário um maior nível de VD iniciado no início da gravidez para prevenção da recorrência dessas doenças no início da vida 75 , mesmo que haja estudos conflitantes ou sem conclusão estatística [76][77][78] . Vários estudos não encontraram evidências positivas da suplementação materna de VD para otimizar a massa óssea da prole 39,[79][80] , embora apresentem evidente melhora das medidas antropométricas 76,81 .…”
Section: Doenças Futuras Na Criançaunclassified